ANALISIS VARIABEL KEUANGAN DAN NON KEUANGAN YANG BERPENGARUH TERHADAP UNDERPRICING INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA - Agus Marimin; Iin Emy Prastiwi; LMS Kristiyanti; Putri Wulan Rahmahwati (ITB AAS INDONESIA, 2023)
This study aims to provide empirical evidence of the influence of firm size (SIZE), rate of return on investment (ROI), financial leverage (FL), earnings per share (EPS), offering size (K), current ratio (CR), Composite stock price index (IHSG), company age (AGE), auditor reputation (AUD), underwriter reputation (IBNK), type of industry (IE), interest rate (SBI) on underpricing in the initial public offering on the IDX. Methods of data analysis using logistic regression, with the results of research on several financial and non-financial variables (company size, rate of return on investment, financial leverage, earnings per share, offering size, current ratio, composite stock price index, company age, auditor reputation, reputation of the underwriter, type of industry, interest rate) variable rate of return on investment that has the most dominant influence on underpricing.